The Passive and Stative Constructions in Ndebele - Langa Khumalo (Nordic Journal of African Studies, 2009)
This paper presents a comparison between the passive and the stative derivations. The stative derivation, which is variously referred to in the literature as the neuter, neuter-passive, quasi-passive, neuter-stative, metastatic-potential, descriptive passive (Satyo 1985), is described by Doke (1947) as closely similar to the passive derivation. Doke (1947) refers to what we will call the stative derivation here as the ‘Middle or Quasi-passive’. This closeness has motivated detailed comparisons of the two derivational forms. While there is no uniformity in the literature as to what the stative derivation is, our choice of the label ‘stative’ is well motivated. As stated in Mchombo (2004: 95), ‘stative’ is based on the observation that the verb denotes the result state of the base verb. It is also a label that is widely used. Mchombo (1993, 2004) looks at the passive and the stative constructions, as two distinct types of verbal extensions, working within the lexicalist theory of syntax, the Lexical Functional Grammar (LFG) theoretical framework. He proposes that the passive morpheme suppresses the agent of the transitive predicate, while the stative morpheme deletes it. Dubinsky and Simango (1996) go further arguing that the passive alters mapping from arguments to grammatical functions, as currently assumed in the Lexical Mapping Theory (henceforth LMT), and the stative performs a perfectly analogous operation on the Lexical Conceptual Structure (LCS), that is argument structure, itself. They present several differences between the two derivations beyond those originally proposed by Mchombo (1993) but are later noted in Mchombo (2004). We use the LMT to analyse the passive and stative derivation in Ndebele. The paper demonstrates that Ndebele deviates from the assumptions arrived at by both Dubinsky and Simango (1996) and Mchombo (1993 & 2004). This paper also demonstrates that the stative derivation is more restricted in Chichewa than is the case in Ndebele.